Foot drop on the opposite side after spinal anesthesia for ankle fracture surgery: a case report - Wendong Zhang; Xingxing Ma; Jiaxin Chen (Journal of International Medical Research, 2023)
Neurological complications after spinal anesthesia have been rarely reported. Persistent neurological dysfunction due to spinal cord or nerve root injury is a serious complication of lumbar anesthesia and manifests as leg pain, numbness, and weakness after initial recovery from anesthesia. We herein report a case of foot drop on the opposite side after spinal anesthesia for ankle fracture surgery. The patient’s symptoms completely disappeared after 3 months, and we consider that her neurological complications were likely caused by the neurotoxicity of local anesthetics.